PENEGAKAN HUKUM PIDANA TERHADAP PEREMPUAN DARI TINDAK PIDANA PERDAGANGAN MANUSIA DI KECAMATAN TENAYAN RAYA - Rendy Rio Pratama; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Human trafficking is a crime that is extraordinary, because impact of human trafficking on the victim and the darting of an environmental bad about. Governments find it difficult to handle the cases of human trafficking, because the perpetrators of the actors using various modes in carrying out the action. in District Tenayan Kingdom trade in human beings handling legal cases less effective, karana in some villages are still many open nightclubs and the localization of the localization tends to occur crime of trafficking in women under age.This type of research to be conducted sociological research that want to see the correlation between law and society, so as to reveal the effectiveness of the rule of law in society. This study bersifatdeskriptif which the author tries to give an idea of the reality of the complete, detailed, and clear about the issues examined. The conclusions that can be drawn from the enforcement of criminal law in the legal protection of women from the crime of trafficking in women in the Police Sector Tenayan Kingdom has not run as it should be proven because their public reports of trafficking cases was revealed.If people do not report these cases may be the case is still going on until today. Factors pengahambat the Police Sector Tenayan Kingdom in enforcing the law against women from the crime of human trafficking victims are just tough questioning. As well as the extent of the districts Tenayan Kingdom who make less than the maximum performance of the police, so that the public report is needed. An attempt by the Police Sector Tenayan Kingdom in addressing cases of human trafficking in the village Maridan District of Tenyan Kingdom improve relations with Waraga living in the border region of Pekanbaru Regency Siak because they in coastal areas are common crimes and dikarnakan them away from the Police Sector Tenayan Kingdom so that people do not want to know the crimes that occur in their territory.Keywords: Law Enforcement - Crime - Human Trafficking